2022
DOI: 10.1111/mec.16397
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length is highly repeatable and shorter in individuals with more elaborate sexual ornamentation in a short‐lived passerine

Abstract: Quantifying an individual's state as a fitness proxy has proven challenging, but accumulating evidence suggests that telomere length and attrition may indicate individual somatic state and success at self‐maintenance, respectively. Sexual ornamentation is also thought to signal phenotypic quality, but links between telomeres and sexual ornamentation have been little explored. To address this issue, we examined whether telomere length and dynamics are predicted by the expression of a sexually selected ornament,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 102 publications
1
8
0
Order By: Relevance
“…Birds that were captured un-ringed were assumed as 1-year old that hatched outside our observed populations. This approach has been used in previous studies (Costanzo et al, 2017;Kauzálová et al, 2022) and is possible because of high breeding philopatry and fidelity of barn swallows. Adult birds that did not return to the breeding locality were presumed dead (Costanzo et al, 2017;Kauzálová et al, 2022).…”
Section: Study Area and General Field Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Birds that were captured un-ringed were assumed as 1-year old that hatched outside our observed populations. This approach has been used in previous studies (Costanzo et al, 2017;Kauzálová et al, 2022) and is possible because of high breeding philopatry and fidelity of barn swallows. Adult birds that did not return to the breeding locality were presumed dead (Costanzo et al, 2017;Kauzálová et al, 2022).…”
Section: Study Area and General Field Proceduresmentioning
confidence: 99%
“…This approach has been used in previous studies (Costanzo et al, 2017;Kauzálová et al, 2022) and is possible because of high breeding philopatry and fidelity of barn swallows. Adult birds that did not return to the breeding locality were presumed dead (Costanzo et al, 2017;Kauzálová et al, 2022). Only resident birds (repeatedly occurring on breeding grounds) with a known year of birth and death were included in the analysis.…”
Section: Study Area and General Field Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Carrying elaborate sexual ornaments is thought to be costly thereby maintaining the honesty of the signal, but there have been few studies done to test the relative cost of ornamentation using telomeres. Kauzálová et al (2022) found that barn swallows Hirundo rustica , with long tail streamers (a sexually selected ornament (Møller, 1988), have shorter telomeres. This suggests a cost to elaborate ornamentation in this species.…”
Section: Telomeres and Life History Trade‐offsmentioning
confidence: 99%
“…Additional studies also emphasize that what qualifies as a stressor depends greatly on the biology of the organism (Friesen et al, 2022; Wood et al, 2022), and demonstrate there is much to be gained by examining telomere dynamics across diverse forms of life (Bae et al, 2022; Boonekamp et al, 2022; McLennan et al, 2022; Power et al, 2022; Rouan et al, 2022). The third suite of articles in this special issue addresses the idea that telomeres may mediate life history trade‐offs, examining correlations between telomere length and reproductive fitness (Heidinger et al, 2022; Kauzálová et al, 2022; Ravindran et al, 2022; Sepp et al, 2022) physical state (e.g., body mass, size: Atema et al, 2022; Le Pepke, Kvalnes, Rønning, et al, 2022), and cancer prevalence (Le Pepke & Eisenberg, 2022; Ujvari et al, 2022) in natural and experimental systems. A final group of manuscripts explores the intriguing nature of heritability of telomere length and rate of shortening (Bauch et al, 2022; Kärkkäinen, Briga, et al 2022; Le Pepke, Kvalnes, Lundregan, et al, 2022; Sparks et al, 2022; Vedder et al, 2022).…”
Section: Highlights Of 2022mentioning
confidence: 99%